Analysis of the Use of Electronic Certificates in Preventing Land Certificate Forgery - Sofyan, Yusuf Sahroni; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to analyze the use of electronic land certificates in preventing land certificate forgery, to analyze the obstacles and solutions to the use of electronic certificates in preventing land certificate forgery. The approach method used is the legislative approach. This type of research is normative juridical research. The type and source of this research data are secondary data. The data analysis method is prescriptive. The results of the study indicate that in dealing with certificate forgery through electronic certificates in the Regulation of the Minister of ATR/BPN No. 1 of 2021 as a form of land modernization. This digitalization is to increase efficiency, transparency, data security, and public trust, while strengthening legal protection and land governance that is more modern and free from illegal practices. In bureaucratic reform, electronic certificates by ATR/BPN are a step in land digitalization to increase efficiency, transparency, and accountability. Its success is influenced by socialization, digital literacy, and apparatus readiness, with challenges such as infrastructure inequality and data security issues. Implementation needs to be gradual and in accordance with the principles of good governance to create modern, safe, and publicly trusted land governance.